Declines in crime and teen childbearing: identifying potential explanations for contemporaneous trends - Colen, Cynthia G. (Journal of quantitative criminology, 2016)
Objectives The previous 25 years have witnessed remarkable upheavals in the social landscape of the United States. Two of the most notable trends have been dramatic declines in levels of crime as well as teen childbearing. Much remains unknown about the underlying conditions that might be driving these changes. More importantly, we do not know if the same distal factors that are responsible for the drop in crime rates are similarly implicated in falling rates of teen births. We examine four overarching potential explanations: fluctuations in economic opportunity, shifting population demographics, differences in state-level public policies, and changes in expectations regarding health and mortality. Methods We combine state and year-specific data from existing secondary sources to model trajectories of violent crime and teen fertility over a 20-year period from 1990 to 2010 using simultaneous fixed-effects regression models. Results We find that 4 of the 20 predictors examined—growth in the service sector of the labor market, increasing racial diversity especially among Hispanics, escalating levels of migration, and the expansion of family planning services to low-income women—offer the most convincing explanations for why rates of violent crime and teen births have been steadily decreasing over time. Moreover, we are able to account for almost a quarter of the joint declines in violent crime and teen births. Conclusions Our conclusions underscore the far reaching effects that aggregate level demographic conditions and policies are likely to have on important social trends that might, at first glance, seem unrelated. Furthermore, the effects of policy efforts designed to target outcomes in one area are likely to spill over into other domains.